Supermarket health advocacy, resources, and education: feasibility of a supermarket-based prediabetes and diabetes screening and education program - Cadzow, Renee; Strohmeier, Andy; Keller, Jamie; Regling, Ashley; Brooks, Marchelle; Quattrin, Teresa (Frontiers in Public Health, 2025)
IntroductionThis project aimed to determine the feasibility of engaging supermarket patrons in diabetes screening, healthy food promotion and education to bridge geographic, economic, and knowledge gaps in diabetes prevention and management.MethodsTrained staff tabled at supermarket entrances advertising screening for pre-diabetes and diabetes. Customers without a diabetes diagnosis completed a National Diabetes Prevention Program Prediabetes Risk Test (score >5 = prediabetes risk). Those with a previous diabetes diagnosis completed a brief questionnaire on their diabetes knowledge/management, healthcare access, and social determinants of health. Surveys took about 5 minutes to complete. Participants received a 5 voucher for fruit and vegetables, evidence based educational material and a list of healthcare resources in the community. The results of the survey informed the design and implementation of 5 educational sessions using an adult learning, popular education approach. A 10 grocery voucher was given for attendance at each session.Results303 customers of four grocery stores in urban Buffalo took the survey between January and June 2024. 67% of those screened were either at-risk for or were already diagnosed with diabetes. 227 people completed the Prediabetes Risk Test: 58% had a score >5 (indicating they were at risk for pre-diabetes), 51% reported having hypertension, and 75% reported a BMI categorized as overweight or obese. 76 participants (25%) stated they had been diagnosed with diabetes. Of these, 91% saw a doctor every 3 months, but 28% did not know the importance of HbA1c, 18% had trouble paying for medications, and 15% had inadequate transportation. 55 people (34 unique) participated in five educational sessions. Participants shared questions, concerns and strategies to overcome barriers to diabetes prevention and control.DiscussionThis project demonstrated that it is feasible to screen for common health conditions in the supermarket setting and that combining screening with immediately accessible healthy food and educational resources can address multiple, intersecting barriers to diabetes prevention and management.